2021
DOI: 10.3389/fncel.2021.735414
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways in Proton and Non-proton ASIC1a Activation

Abstract: Acid-sensing ion channels (ASICs) regulate synaptic activities and play important roles in neurodegenerative diseases as well as pain conditions. Classically, ASICs are described as transiently activated by a reduced pH, followed by desensitization; the activation allows sodium influx, and in the case of ASIC1a-composed channels, also calcium to some degree. Several factors are emerging and extensively analyzed as modulators, activating, inhibiting, and potentiating specific channel subunits. However, the sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…This Nu fraction was heavily phosphorylated, as has been documented before and shown in Supplementary Figure S1C. The importance of ERK in signaling cascades has been widely studied as a master switch [25] and player involved in the downstream signaling of ASIC1a activation [26]. This work provides additional tools to further characterize these mechanisms.…”
Section: Discussionsupporting
confidence: 71%
“…This Nu fraction was heavily phosphorylated, as has been documented before and shown in Supplementary Figure S1C. The importance of ERK in signaling cascades has been widely studied as a master switch [25] and player involved in the downstream signaling of ASIC1a activation [26]. This work provides additional tools to further characterize these mechanisms.…”
Section: Discussionsupporting
confidence: 71%
“…Okine et al documented the activation of ERK at the ACC in the formalin rat model connected to the G-protein coupled receptor, GPR5, with endogenous activation of GPR55 signaling and increased ERK phosphorylation in the ACC facilitating inflammatory pain via top-down modulation of descending pain control [26]. The phosphorylation of the ERK kinase has also been linked to the activation of ASIC1 channels [19,30]. We showed that ASIC1 channels contribute to the ERK signaling pathway in this pain model (Figure 3B and Figure S1) which further links the channel to the pain pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We previously documented the contribution of ASIC1a channels to the activation of the ERK pathway [18,19]. This pathway is recognized as one involved in pain [20][21][22][23][24][25].…”
Section: Signaling Down-stream Asic1amentioning
confidence: 99%
“…This stabilization of the open state can be shown on the potentiation of the ASIC2a current by MitTx, involving a drastic shifting of its pH-dependent activation curve towards less acidic pH (pH 0.5 shifted from 3.5 to 6.0) [ 99 ]. The overlap of the binding between MitTx-β and PcTx1 on the thumb domain explains why the binding and biological activity of MitTx and PcTx1 are mutually exclusive [ 99 , 140 ].…”
Section: Dual Effects Of Animal Toxins Targeting Asicsmentioning
confidence: 99%